Perancangan Sistem Informasi Pemesanan Tiket Bus pada PT. Putra Pelangi Perkasa - Yudhistira Adhitya Pratama; Okky Putra Barus; Faisal Nadjar; Sherin Karisa; Jefri Junifer Pangaribuan (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
PT. Putra Pelangi Perkasa is one of the companies engaged in AKAP (Inter-City Inter-Provincial) passenger transportation services. In supporting its business, the company has a website-based information system, namely https://www.putrapelangi.com/. However, the website currently used by the company is only specifically used for internal companies. Customers who will order tickets are still done conventionally by visiting the company counter directly so that this process is very ineffective and efficient. Therefore, by designing a website-based information system for ordering bus tickets for PT. Putra Pelangi Perkasa can solve problems in the current system. This system was designed using Balsamiq Mockups 3 and the Unified Modeling Language (UML) system modeling using the Laravel framework. The method of testing this system is black-box and the results of the study show that the bus ticket booking information system that was built is very effective and efficient for use in ordering bus tickets because of the search, ordering, payment, cancellation of bus tickets, and seeing the available seat plans. visualization of the system being built.